The factors influencing the successful development of safety culture in RISDA Melaka / Nurhuda Kassim - Kassim, Nurhuda (Faculty of Business and Management, 2010)
Most injuries are not caused by faulty equipment; they are caused by an employee’s behavior. Safety culture is a term often used to describe the way in which safety is managed in the workplace, and often reflects the attitude, beliefs, perceptions and values that employees share in relation to safety: (Cox and Cox, 1991). This research is about the factors that influencing the successful development of a safety culture. The research is based in RISDA Melaka. In this project paper the main aims of this research is to study the factors that will influence the development of safety culture. This research involves 100 staff of RISDA Melaka. Three factors will be use to determine the successful development of a safety culture which is, safety programmes work, maintenance, and employee empowerment. The factors are being identified in order to make an investigation whether or not these factor have significantly and influence the successful development of a safety culture at RISDA, Melaka. In this study, the method use is questionnaire. It will be use to identify the relevant information regarding the study on perception of safety culture at RISDA Melaka. Researchers also use secondary data such as journals, previous thesis, article and internal data.